2006
DOI: 10.1292/jvms.68.171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Borna Disease Virus Antibodies in Healthy Japanese Black Cattle in Kyushu

Abstract: ABSTRACT. Epidemiological studies have demonstrated that asymptomatic infection of Borna disease virus (BDV) is found in various species of animals in Japan. Recent reports have also revealed that neurological diseases caused by this virus could exist in horses, cattle, a dog, and cats in this country. In this study, we investigated seroprevalence of BDV antibodies in Japanese black cows reared in Kyushu, the southernmost main island of Japan, using ELISA and Western-immunoblotting. Of 101 serum samples, 11 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…However, the conflicting results regarding BDV infection cannot be attributed only to geographic factors. It has been reported that BDV is not associated with psychiatric patients in Kyushu island in Japan, a known endemic area of BDV infection 8,42,49. However, there have been two BDV-positive reports in Brazil, which has not been known to be an endemic BDV infection area 23,24.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the conflicting results regarding BDV infection cannot be attributed only to geographic factors. It has been reported that BDV is not associated with psychiatric patients in Kyushu island in Japan, a known endemic area of BDV infection 8,42,49. However, there have been two BDV-positive reports in Brazil, which has not been known to be an endemic BDV infection area 23,24.…”
Section: Discussionmentioning
confidence: 97%
“…BDV is a highly neurotropic RNA virus with an enveloped, nonsegmented, negative stranded RNA genome 2-4. BDV has been known to naturally infect several animal species such as cattle, cats, horses, and sheep 5-8…”
Section: Introductionmentioning
confidence: 99%
“…As we used the same primers as in the previous report [31], the lack of BoDV-1 detection in this study should not be due to the sensitivity of PCR, or due to the sampling site, since serologically positive cases and detection of BoDV-1 genome fragment in mammals have been reported for the same sampling sites in Japan [33,34]. Together with the fact that there have been only a few reports of BoDV-1 detected in birds in the last several decades [30,31], our data suggest that the possibility of BoDV-1 infection in birds is rare, at least at our sampling sites in Japan.…”
Section: Discussionmentioning
confidence: 86%
“…Symptoms other than encephalitis, such as infertility or astasia, has been confirmed in antibody-positive cows [1]. Borna disease in both domestic animals and companion animals has been reported in Japan [3,4,5, 7, 8, 13,14,15, 25]; however, epidemiological studies of cattle are lacking. There are few studies on the mode of transmission of this virus in cattle, and many questions remain surrounding infection.…”
mentioning
confidence: 99%